2022
DOI: 10.1021/acsomega.2c01216
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure Optimization of PdZn-Graphitic Carbon Nitride Nanocomposites as Electrocatalysts for Selective CO2 to CO Conversion

Abstract: Herein, a novel PdZn/g-C 3 N 4 nanocomposite electrocatalyst, PdZnGCN, prepared from a facile hydrothermal reduction procedure for an efficient CO 2 to CO conversion has been examined. This composite catalyst reduces CO 2 at a thermodynamic overpotential of 0.79 V versus RHE with a 93.6% CO Faradaic efficiency and a CO partial current density of 4.4 mA cm –2 . Moreover, the turnover frequency for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…As shown in Figure 3a−d,g,h, the Pd 3d peaks for the ternary CuZnPd-1, binary CuPd, and ZnPd alloy nanoparticles, as well as the commercial Pd/C catalyst, and the Cu 2p peaks of the ternary CuZnPd-1 and binary CuPd alloy nanoparticles could be deconvoluted into two pairs of doublets, in which the more intense doublet could be assigned to the metallic Pd and Cu, while the weaker doublet is attributed to the oxidized Pd and Cu. 24,27,28,31,46 For the Zn 2p peaks of the ternary CuZnPd-1 and binary ZnPd alloy nanoparticles (Figure 3e,f), only two peaks attributed to metallic Zn 2p 1/2 and Zn 2p 3/2 , respectively, could be identified. 46 Notably, the binding energies of the Pd 3d peak for CuPd nanoparticles display an evident positive shift relative to those of the Pd 3d peak for commercial Pd/C (Figure 3b,d), which might be ascribed to the compressive lattice strain of Pd by alloying with Cu, 24,27,29,31,33,34 and the electron flow from Pd to Cu, possibly owing to the half empty 4s band of Cu.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3a−d,g,h, the Pd 3d peaks for the ternary CuZnPd-1, binary CuPd, and ZnPd alloy nanoparticles, as well as the commercial Pd/C catalyst, and the Cu 2p peaks of the ternary CuZnPd-1 and binary CuPd alloy nanoparticles could be deconvoluted into two pairs of doublets, in which the more intense doublet could be assigned to the metallic Pd and Cu, while the weaker doublet is attributed to the oxidized Pd and Cu. 24,27,28,31,46 For the Zn 2p peaks of the ternary CuZnPd-1 and binary ZnPd alloy nanoparticles (Figure 3e,f), only two peaks attributed to metallic Zn 2p 1/2 and Zn 2p 3/2 , respectively, could be identified. 46 Notably, the binding energies of the Pd 3d peak for CuPd nanoparticles display an evident positive shift relative to those of the Pd 3d peak for commercial Pd/C (Figure 3b,d), which might be ascribed to the compressive lattice strain of Pd by alloying with Cu, 24,27,29,31,33,34 and the electron flow from Pd to Cu, possibly owing to the half empty 4s band of Cu.…”
Section: Resultsmentioning
confidence: 99%
“…24,27,28,31,46 For the Zn 2p peaks of the ternary CuZnPd-1 and binary ZnPd alloy nanoparticles (Figure 3e,f), only two peaks attributed to metallic Zn 2p 1/2 and Zn 2p 3/2 , respectively, could be identified. 46 Notably, the binding energies of the Pd 3d peak for CuPd nanoparticles display an evident positive shift relative to those of the Pd 3d peak for commercial Pd/C (Figure 3b,d), which might be ascribed to the compressive lattice strain of Pd by alloying with Cu, 24,27,29,31,33,34 and the electron flow from Pd to Cu, possibly owing to the half empty 4s band of Cu. 22,32 However, the binding energies of the Pd 3d peak for the binary ZnPd alloy nanoparticles have an obvious negative shift relative to that for the commercial Pd/C catalyst (Figure 3c,d) owing to the electron flow from Zn to Pd due to the larger work function of Pd than that of Zn.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that rate-determining steps (RDS) may be (3) or (4), depending on the COOH* binding energy and the CO* desorption energy. [41,42] Therefore, the accurate regulation of the adsorption strength of key intermediates is fairly essential to exploit the reasonable electrocatalyst for reducing CO 2 to CO. [43,44] Notably, except the ECR process, hydrogen adsorption on the electrocatalyst surface needs to be considered, because that HER is the main competitor of ECR. Stronger H* binding ability is required to rise HER overpotential, which will help promote the occurrence of ECR.…”
Section: Mechanism From Co 2 To Comentioning
confidence: 99%
“…Converting carbon dioxide (CO 2 ) into valuable chemicals and fuels has made an impact on reducing our carbon footprint. However, the high stability of CO 2 for conversion into different chemicals restricts the application. Therefore, the research community has focused on developing materials and systems for efficient CO 2 conversion by reducing the high activation energy of CO 2 . It is possible to achieve CO 2 reduction via various routes, including photocatalytic and electrochemical conversion. In this way, besides decreasing carbon emissions, value-added chemicals, such as methanol, hydrogen, formic acid, and syngas, can be produced. Among these chemicals, formic acid stands out as an alternative to fossil fuels due to its advantages, such as being an energy-intensive material, having a high volumetric hydrogen density, and having enormous potential as an effective hydrogen storage vector . Typically, the most important factor in producing different types of chemicals, from formic acid to carbon monoxide and multicarbon hydrocarbons and oxygenates, is the selectivity of the used catalyst.…”
Section: Introductionmentioning
confidence: 99%